2021
DOI: 10.24251/hicss.2021.068
|View full text |Cite
|
Sign up to set email alerts
|

A Matter of Trust? Examination of Chatbot Usage in Insurance Business

Abstract: Critical success factors such as trust and privacy concerns have been recognized as grand challenges for research of intelligent interactive technologies. Not only their ethical, legal, and social implications, but also their role in the intention to use these technologies within high risk and uncertainty contexts must be investigated. Nonetheless, there is a lack of empirical evidence about the factors influencing user's intention to use insurance chatbots (ICB). To close this gap, we analyze (i) the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 39 publications
5
27
0
2
Order By: Relevance
“…Therefore, it is essential to consider user's gratification elements in determining the acceptance of novel technologies such as chatbots. Besides, literature related to technology acceptance showed that privacy concern hinders the acceptance of technology (Rodr ıguez Cardona et al, 2021); therefore, it is also an important element to address the acceptance of chatbot. The study by Fernandes and Oliveira (2021) also called future studies to address consumer acceptance of using automated technologies Chatbots in the frontline by considering the elements of user gratification and privacy.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is essential to consider user's gratification elements in determining the acceptance of novel technologies such as chatbots. Besides, literature related to technology acceptance showed that privacy concern hinders the acceptance of technology (Rodr ıguez Cardona et al, 2021); therefore, it is also an important element to address the acceptance of chatbot. The study by Fernandes and Oliveira (2021) also called future studies to address consumer acceptance of using automated technologies Chatbots in the frontline by considering the elements of user gratification and privacy.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For chatbots, customers assume that using chatbots will improve productivity and performance Chatbots in the frontline (Ashfaq et al, 2020), which leads to acceptance of chatbots. A few other empirical studies also argued that perceived usefulness significantly affects the intention to use chatbots (Patil and Kulkarni, 2019;Rodr ıguez Cardona et al, 2021). The importance of perceived usefulness related to the use of chatbot service and how it builds a positive attitude have been discussed in the literature (Brandtzaeg and Følstad, 2017;Zarouali et al, 2018).…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%
See 1 more Smart Citation
“…B. Rodríguez Cardona et al. 2021 ) sowie sogenannte Wearables (z. B. Fitnessarmbänder) im Rahmen verhaltensbasierter Tarife (z.…”
Section: Einordnung Digitaler Finanzassistenten In Theorie Und Praxisunclassified
“… 2019 ; Rodríguez Cardona et al. 2021 ). Zudem zeigen andere Studien, dass neben der Nutzenerwartung auch die Kompatibilität mit dem persönlichen Lebensstil sowie die individuelle Innovationsbereitschaft positiv auf die Nutzungseinstellung gegenüber dem Angebot digitaler Finanzdienstleistungsservices wirken (z.…”
Section: Empirische Untersuchung Der Nutzungseinstellung Zu Digitalen...unclassified